'What kind of democracy is this?': Conscientious objectors to the National Service Schemes - Oliver, Bobbie (Black Swan Press, 2014)
This chapter examines a different kind of sacrifice – that made by young men who went contrary to the tide of popular opinion to make a stand against conscription for military service, and in particular, conscription for active service overseas in the Vietnam War. Historians have often portrayed Australians as a nation eager to go to war, especially on behalf of ‘a powerful ally’ such as Britain or the United States of America – an assumption based on the thousands who willingly enlisted in both world wars, and the public scorn directed at those who stayed home. Despite this perception being challenged by Australia’s involvement in an increasingly unpopular war in Vietnam, conscientious objectors still suffered social stigma, loss of employment and economic hardship as well as long periods in prison.